Low temperature increased the biosynthesis of 2-AP, cooked rice elongation percentage and amylose content percentage in rice. (May 2020) - Okpala, Nnaemeka Emmanuel; Potcho, Mouloumdema Pouwedeou; An, Tianyue; Ahator, Stephen Dela; Duan, Lixin; Tang, Xiangru
Abstract: Rice fragrance, cooked rice elongation and amylose content are some of the traits used in determining rice grain quality. 2-acetyl-1-pyrroline (2-AP) is the major compound that is responsible for fragrance in rice. This experiment was conducted with two indica rice cultivars: Meixiangzhan 2 and Xiangyaxiangzhan. Three temperature-controlled chambers: High (32 °C from 06:00 to 17:59 and 26 °C from 18:00 to 05:59), medium (27 °C from 06:00 to 17:59 and 21 °C from 18:00 to 05:59) and low (22 °C from 06:00 to 17:59 and 16 °C from 18:00 to 05:59) were used for the study. At the onset of heading, both cultivars were transferred to the three temperature-controlled chambers. Our results showed that in both cultivars, low temperature growth had the highest 2-AP content, while high temperature growth recorded the lowest 2-AP content. Principal component analysis showed remarkable differences in the metabolomes of rice grown in high, medium and low regimes. In the grains of both cultivars, we observed significant reduction in 2-AP content after 6 and 9 months of storage, however; 2-AP retention differed greatly in both cultivars. We also reported that low temperature growth increased cooked rice elongation percentage and the biosynthesis of amylose in rice. In conclusion, our findings will provide more information to breeders working on the improvement of rice grain quality. Graphical abstract: Image 1 Highlights: The results reported here, show that low temperature increased the biosynthesis of 2-AP in rice. 2-AP content in rice grains decreased gradually over nine months of storage. We also showed that low temperature increased cooked rice elongation percentage and the biosynthesis of amylose in rice.